COCCYDYNIA: A NARRATIVE REVIEW OF PATHOPHYSIOLOGY, ETIOLOGY AND TREATMENT - Ezgi Akar; Ahmet Öğrenci; Sedat Dalbayrak (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2023)
Pain and discomfort in the coccyx or tailbone area is called as coccydynia or coccygodynia. Despite its small size, the coccyx, which forms the terminal of the spine, has an important role to support the balanced distribution of body weight, especially in the sitting position, due to its relationship with the surrounding muscles, ligaments and bone structures. The problems of this area for various reasons manifests itself with localized discomfort and pain in the sacrococcygeal region. Our aim in this paper is to review the etiology, pathophysiology, clinical findings, diagnosis and treatment methods of coccydynia in light of the current literature.